General principles of drugs administration and nursing procedures - Laganá, Maria Teresa Cícero; Araújo, Thelma Leite de; Santos, Leila Conceição Rosa dos; Silva, Sandra Honorato da (Revista da Escola de Enfermagem da USP, 1989)
The authors analyse the responsability of the nurse during the administration of drugs and solutions. Three aspects are approached: the ethic aspects of professional attitudes, scientifics and iatrogenics.